2016
DOI: 10.3847/0004-637x/831/1/24
|View full text |Cite
|
Sign up to set email alerts
|

Hinode and Iris Observations of the Magnetohydrodynamic Waves Propagating From the Photosphere to the Chromosphere in a Sunspot

Abstract: Magnetohydrodynamic (MHD) waves have been considered as energy sources for heating the solar chromosphere and the corona. Although MHD waves have been observed in the solar atmosphere, there are a lack of quantitative estimates on the energy transfer and dissipation in the atmosphere. We performed simultaneous Hinode and IRIS observations of a sunspot umbra to derive the upward energy fluxes at two different atmospheric layers (photosphere and lower transition region) and estimate the energy dissipation. The o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 57 publications
8
30
0
Order By: Relevance
“…The latter value would be 765± 57erg cm −2 s −1 if the alternative height (1500 km), inferred from the phase difference spectra, is assumed for the IRIS1330 Å channel. In either case, these values indicate significant damping in agreement with Kanoh et al (2016). Of course, it is not trivial to state whether or not the entire missing wave energy directly resulted in the thermalization of the local plasma.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The latter value would be 765± 57erg cm −2 s −1 if the alternative height (1500 km), inferred from the phase difference spectra, is assumed for the IRIS1330 Å channel. In either case, these values indicate significant damping in agreement with Kanoh et al (2016). Of course, it is not trivial to state whether or not the entire missing wave energy directly resulted in the thermalization of the local plasma.…”
Section: Discussionsupporting
confidence: 66%
“…Felipe et al (2011) found an energy flux of the order of 10 6 erg cm −2 s −1 at photospheric heights, and concluded that the energy flux available from acoustic oscillations is insufficient to balance the radiative losses in chromospheric umbrae. Recently, using simultaneous observations of a sunspot umbra with Hinode (Kosugi et al 2007) and IRIS, Kanoh et al (2016) estimated the energy fluxes for 6-10 mHz SMAWs at the photospheric and lower transition region levels as 2×10 7 erg cm −2 s −1 and 8.3×10 4 erg cm −2 s −1 , respectively. These results, in contrast to Felipe et al (2011), demonstrate the potential for SMAWs to contribute significantly to the heating of the umbral chromosphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We set δv and f 0 to 0.4 km s −1 and 5 mHz, respectively. Furthermore, f 0 is set close to the most dominant frequency of the chromospheric longitudinal waves (Tian et al 2014;Kanoh et al 2016).…”
Section: Photospheric Boundary Conditionmentioning
confidence: 99%
“…Although there have been many studies of MHD waves in the last few decades, observations about the propagating wave taken by the IRIS are rarely reported (Okamoto et al 2015). Over the solar disk, there are only a few published results of chromospheric waves from the IRIS data (Bryans et al 2016;Kanoh et al 2016). One important reason is that there are so many fine structures in the chromosphere, thus making it difficult to detect the wave signal in a particular chromospheric structure among the abundant features.…”
Section: Introductionmentioning
confidence: 99%